Soft wheat: quality of flour and grain, price - A. V. Alabushev; M. M. Kopus; T. S. Makarova (Зерновое хозяйство России, 2020)
In recent years the Russian Federation is among the world's leading grain producers. The country is considered a world leader in export of wheat. Russian wheat in the world market attracts with its price and quality. How is high-quality wheat flour valued in the domestic market, in multiple shops? To study the problem, there were purchased flour samples in such multiple shops as Magnit, Record and SuperU (France), as well as flour of local production in AO “Uchkhoz Zernovoye” (Zernograd). We evaluated flour quality not only according to the information indicated on the packages, but also there were conducted analysis in our own laboratory (on protein percentage, SDS sedimentation, grain prolamins). The study results showed that protein content in flour was actually more by 0.3–2.9% (except “Farine de ble T-65”), which in terms of grain (cake meal) corresponded to grain of 1–3 class. According to SDS-sedimentation, all flour samples corresponded to the traits of “strong” and “valuable” wheat, except for rye flour and a special product “Pudov (French recipe)”. The gliadins in the studied samples were rated as “good” and “+”, “-”. Consequently, the price of premium baking flour was formed not only due to its quality, but also according to the brand's popularity (“MAKFA”, “Pudov”), according to supply and demand, and it sometimes differs twofold e. g. “Petrovsky niva” costs 22.45 rubles per kg., “MAKFA” costs 42.90 rubles per kg.